SOSIALISASI UPAYA PENCEGAHAN DAN PENANGGULANGAN BULLYING DI UPT SD NEGERI 16 SIDOMULYO SUATU KAJIAN EDUKASI DAN INTERVENSI SEKOLAH DASAR - Dinda Fania Ardhini; Manda Azzahra; Fatur Najah SR; Putri Handayani; Syaibatul Marwah Situmorang; Fita Fitria; Rizqy Fadhlina Putri (LPPI UMN AL WASHLIYAH, 2026)
Bullying is a serious issue in primary schools that can negatively affect students’ mental health and academic performance. This study aims to examine the prevention and intervention efforts against bullying at UPT SD Negeri 16 Sidomulyo through education and school-based programs. The research employed a case study method with a qualitative approach using interviews, observations, and policy analysis. The findings reveal that the school has implemented various measures, such as awareness campaigns, the formation of an anti-bullying team, and extracurricular activities that promote positive peer relationships. These efforts have increased students’ awareness, encouraged reporting, and strengthened coordination between teachers and parents. However, challenges remain, including a lack of full awareness among some students and teachers as well as limited parental involvement. Enhancing outreach and collaboration is essential to creating a safe, comfortable, and inclusive school environment.